THE INFLUENCE OF INFOGRAPHIC MEDIA ON STUDENTS' INTEREST IN LEARNING HISTORY IN CLASS X SMA NEGERI 1 KUNDUR: Pengaruh Media Infografis Terhadap Minat Belajar Siswa pada Pembelajaran Sejarah di Kelas X SMA Negeri 1 Kundur - Isjoni; Asril; Yeni Anggraeni (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Students' interest in learning history remains low, primarily due to limited variety in instructional media. History education requires media that can present complex information in an engaging and accessible manner. Infographic media offers effective visualization to enhance students' learning interest. This study aims to determine the influence of infographic media on students' interest in learning history in class X of SMA Negeri 1 Kundur. This research employed a quantitative quasi-experimental design with a nonequivalent control group. The sample consisted of 68 students divided into a control class (n=34) using conventional PowerPoint media and an experimental class (n=34) using infographic media. The research instrument was a learning interest questionnaire with 25 valid items (α=0.874). Data were analyzed using independent sample t-test via SPSS version 25. Results showed a significance value of 0.026 (p<0.05), indicating a significant influence of infographic media on students' learning interest. The mean posttest score of the experimental class (M=103.91; SD=6.186) was significantly higher than the control class (M=100.18; SD=7.313). Cohen's d value of 0.55 indicates moderate effect size. This study demonstrates that infographic media effectively enhances students' learning interest in history with moderate practical significance.